Synthesis, characterization and some optical properties of silver nanoparticles prepared by pulsed Laser ablation technique (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare silver nanoparticles by laser ablation method in an aqueous medium to dements rate the important of laser in the production of silver nanoparticles , AgNPS prepared were distinguished by their structural , physical and optical properties . so we studied the properties of these nanoparticles prepared in this way . some optical examinations were performed on the colloidal silver solution , the structural properties were characterized by using X-Ray diffraction , the physical properties were analyzed by Field Emission Scanning Electron Microscopy( FESEM ) and the optical Properties were analyzed by UV-Visible spectroscopy , and FTIR measurement in order to identify the dimensions , and shapes of the prepared AgNPS .and used Energy - Dispersive X- Ray Spectroscopy ( EDX ) , Fluorescence Spectrum measurement , these particles were prepared by means of a liquid-pulsed laser ablation technique (PLAL) using Nd:YAG laser with an energy of ( 500 ) mj . And a number 0f (100 ) pulses . this method is simple , pollution , free , stable , and has the ability to determine the specifications of the prepared particles. when examining the size and shape of the nanoparticles it was found that the nanoparticles are spherical shape , which dimensions ranging (46.55- 34.80) nm .The optical properties were also studied by UV-Visible spectroscopy ,the results showed that the absorption spectrum of silver was located at ( 534 ) nm . the height and decrease of the absorption peaks depend on the concentration of silver nanoparticles in the colloidal solution , as well as the shape of those particles . the results of X-Ray diffraction examination showed that the film of the prepared AgNps at energy ( 500 ) mj is polycrystalline and of cubic type .